2013
DOI: 10.1177/0047117813497306
|View full text |Cite
|
Sign up to set email alerts
|

EU external policy at the crossroads: The challenge of actorness and effectiveness

Abstract: The goal of this Special Issue is to improve our conceptualisation and empirical understanding of EU actorness and effectiveness in International Relations. While the European Union aspires to play a greater global role, its actorness and effectiveness cannot be taken for granted given the nature of the EU as a multi-level and semi-supranational polity encompassing 28 Member States with diverse foreign policy preferences. The EU is presently at an important crossroad. On the one hand, its external policy statu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
50
0
3

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 109 publications
(53 citation statements)
references
References 17 publications
(28 reference statements)
0
50
0
3
Order By: Relevance
“…Others show how growing capabilities, preferences and entrepreneurship lead to more emancipation of the agent from principals (Niemann and Huigens 2011). Yet others investigate how agents are able to weaken principals' incentives to control (Delreux and Kerremans 2010;Heldt 2017), how national administrations maintain their capacity to control the agent (Adriaensen 2016), and how internal cohesiveness together with the bargaining context shapes the external effectiveness of the EU in trade negotiations (Conceição-Heldt 2014;Elsig 2013;Niemann and Bretherton 2013). This contribution complements the other chapters assembled in this edited volume, for example Niemann and Plank's study of the conditions under which agents are more likely to acquire more discretion vis-à-vis the principals (Plank and Niemann this volume), Helwig's examination of how agent interaction affects the EU High Representative's level of discretion (Helwig this volume) and Kroll's piece on the Council having different mechanisms of control at its disposal to control the European Council (Kroll this volume).…”
mentioning
confidence: 99%
“…Others show how growing capabilities, preferences and entrepreneurship lead to more emancipation of the agent from principals (Niemann and Huigens 2011). Yet others investigate how agents are able to weaken principals' incentives to control (Delreux and Kerremans 2010;Heldt 2017), how national administrations maintain their capacity to control the agent (Adriaensen 2016), and how internal cohesiveness together with the bargaining context shapes the external effectiveness of the EU in trade negotiations (Conceição-Heldt 2014;Elsig 2013;Niemann and Bretherton 2013). This contribution complements the other chapters assembled in this edited volume, for example Niemann and Plank's study of the conditions under which agents are more likely to acquire more discretion vis-à-vis the principals (Plank and Niemann this volume), Helwig's examination of how agent interaction affects the EU High Representative's level of discretion (Helwig this volume) and Kroll's piece on the Council having different mechanisms of control at its disposal to control the European Council (Kroll this volume).…”
mentioning
confidence: 99%
“…Internal cohesiveness does not automatically translate into more external effectiveness (Elsig 2013;Niemann and Bretherton 2013;Smith 2010b;Thomas 2012). Recent studies have shown this to be the case especially in foreign policy.…”
Section: Configuration 2: Internal Cohesiveness Has No Impact On Extementioning
confidence: 99%
“…More recent conceptualizations from International Relations literature define external effectiveness in terms of actors' 'ability to realize the goals they set for themselves' (Acharya and Johnston 2007: 13). Literature on European integration is now starting to employ the concept of external effectiveness defined as the EU's ability to reach its objectives by influencing other actors (Laatikainen and Smith 2006;Niemann and Bretherton 2013;Van Schaik 2013).…”
Section: External Effectiveness: Definitionmentioning
confidence: 99%
See 2 more Smart Citations